1995
DOI: 10.1128/jb.177.13.3808-3817.1995
|View full text |Cite
|
Sign up to set email alerts
|

Supraoperonic clustering of pca genes for catabolism of the phenolic compound protocatechuate in Agrobacterium tumefaciens

Abstract: The protocatechuate branch of the ␤-ketoadipate pathway comprises the last six enzymatic steps in the catabolism of diverse phenolic compounds to citric acid cycle intermediates. In this paper, the regulation and tight supraoperonic clustering of the protocatechuate (pca) genes from Agrobacterium tumefaciens A348 are elucidated. A previous study found that the pcaD gene is controlled by an adjacent regulatory gene, pcaQ, which encodes an activator. The activator responded to ␤-carboxy-cis,cis-muconate and was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 51 publications
(75 reference statements)
3
58
0
Order By: Relevance
“…There are 12 protein-coding genes that have been identified as being part of this pathway in B. suis 1330 (44); all of them are found on chromosome 2. In the case of Agrobacterium tumefaciens C58, the enzymes involved in this pathway are organized into two distinct operons (43); Brucella seems to have a similar arrangement, as do both Ochrobactrum genomes. Examination of all 10 Brucella genomes showed that at least 1 of the 12 genes carried by every genome except B. suis 1330 has become a pseudogene and that both of these operons are completely missing in B. suis ATCC 23445 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There are 12 protein-coding genes that have been identified as being part of this pathway in B. suis 1330 (44); all of them are found on chromosome 2. In the case of Agrobacterium tumefaciens C58, the enzymes involved in this pathway are organized into two distinct operons (43); Brucella seems to have a similar arrangement, as do both Ochrobactrum genomes. Examination of all 10 Brucella genomes showed that at least 1 of the 12 genes carried by every genome except B. suis 1330 has become a pseudogene and that both of these operons are completely missing in B. suis ATCC 23445 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4. Structures of gene clusters for the catabolism of protocatechuate and 4-sulfocatechol from H. intermedia S1 and A. radiobacter S2 in comparison to the protocatechuate gene clusters from R. opacus, Acinetobacter calcoaceticus, P. putida and Agrobacterium tumefaciens (Eulberg et al, 1998;Parke, 1995). (Page, 1996).…”
Section: Turnover Of 3-sulfomuconate By Hicmle2 and Arcmle2mentioning
confidence: 99%
“…The first step in the metabolism of these compounds involves their conversion into either protocatechuate or catechol, which is subsequently metabolized to tricarboxylic acid intermediates via the ␤-ketoadipate pathway (18). This metabolic pathway has been documented in many members of the family Rhizobiaceae (23,35,(38)(39)(40), suggesting that the ␤-ketoadipate pathway is important for the survival of these soil-dwelling microorganisms.Sinorhizobium meliloti is a gram-negative, soil-dwelling bacterium that participates in a symbiotic relationship with the legume alfalfa through the establishment of nitrogen-fixing root nodules. Enzymes involved in the protocatechuate branch of the ␤-ketoadipate pathway in S. meliloti are encoded within the pcaDCHGB and pcaIJF operons, which are subject to regulation by products encoded by pcaQ and pcaR, respectively (23).…”
mentioning
confidence: 99%
“…The first step in the metabolism of these compounds involves their conversion into either protocatechuate or catechol, which is subsequently metabolized to tricarboxylic acid intermediates via the ␤-ketoadipate pathway (18). This metabolic pathway has been documented in many members of the family Rhizobiaceae (23,35,(38)(39)(40), suggesting that the ␤-ketoadipate pathway is important for the survival of these soil-dwelling microorganisms.…”
mentioning
confidence: 99%